Whither economic duress? Reflections on two recent cases - PHANG, Andrew B.L. (Institutional Knowledge at Singapore Management University, 1990)
From its rather tentative and extremely recent beginnings, I the law relating to economic duress has developed at a relatively rapid pace during the last decade or so. We have had a series of decisions from various courts and jurisdictions* which, collectively at least, affirm the existence of the doctrine in English law. The pronouncements at the highest levels, however, have not purported to be definitive, and, as we shall see, have certainly not aided in a clarification and systematization of the doctrine of economic duress. The two recent decisions, which are the subject of the present comment, have merely underscored the very urgent need for a bolder and more definitive approach toward this dynamic area of the common law Since the factual nature of the doctrine is of special importance, it is appropriate to begin with the essential facts of each case.